2023
DOI: 10.1177/09603271231173378
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnetin alleviates polystyrene microplastics-induced testicular damage by restoring biochemical, steroidogenic, hormonal, apoptotic, inflammatory, spermatogenic and histological profile in male albino rats

Abstract: The current research was performed to evaluate the ameliorative effects of Rhamnetin (RHM) on polystyrene microplastics (PS-MPs)-instigated testicular dysfunction in male albino rats. 48 albino rats were distributed in four groups, i.e., control, PS-MPs treated, PS-MPs + RHM co-treated and RHM only supplemented group. PS-MPs exposure considerably reduced anti-oxidant enzymes i.e., catalase (CAT), glutathione peroxidase (GSR), superoxide dismutase (SOD) and glutathione reductase (GPx) activities. Whereas, react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 71 publications
1
1
0
1
Order By: Relevance
“…A previous study of PS-MPs orally administrated to rats supported our findings, which showed histopathological changes and morphometric alternations in exposed testis (Ijaz et al, 2021). Additionally, this histopathological alternation has been reported in a recent study of orally administrated PS-MPs in rats (Hamza et al, 2023).…”
Section: Notesupporting
confidence: 91%
“…A previous study of PS-MPs orally administrated to rats supported our findings, which showed histopathological changes and morphometric alternations in exposed testis (Ijaz et al, 2021). Additionally, this histopathological alternation has been reported in a recent study of orally administrated PS-MPs in rats (Hamza et al, 2023).…”
Section: Notesupporting
confidence: 91%
“…Em relação aos marcadores apoptóticos, houve um aumento na expressão de Bax e Caspase-3, enquanto observou-se uma diminuição nos marcadores anti-apoptóticos, como Bcl-2. Além disso, foi observada uma diminuição do hormônio luteinizante e do hormônio folículo-estimulante, bem como os níveis plasmáticos de testosterona (HAMZA et al, 2023;IJAZ et al, 2023;SARASAMMA et al, 2020). (FENG et al, 2022;LI et al, 2022).…”
Section: Resultsunclassified
“…Spermatogenesis is a cascade of events that is regulated under the influence of hormones of hypothalamic pituitary gonadal axis (HPG). [56][57][58] Hypothalamus discharges the gonadotropin-releasing hormone (GnRH) that instigates the liberation of FSH and LH (gonadotropins), which are crucial for reproduction. FSH is responsible for the proper functioning of Sertoli cells (SCs) that make and discharge regulatory molecules and nutrients required for spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%